Interferon-γ exposure of human iPSC-derived neurons alters major histocompatibility complex I and synapsin protein expression - Pavlinek, Adam; Matuleviciute, Rugile; Sichlinger, Laura; Dutan Polit, Lucia; Armeniakos, Nikolaos; Vernon, Anthony Christopher; Srivastava, Deepak Prakash (Frontiers in Psychiatry, 2022)
Human epidemiological data links maternal immune activation (MIA) during gestation with increased risk for psychiatric disorders with a putative neurodevelopmental origin, including schizophrenia and autism. Animal models of MIA provide evidence for this association and suggest that inflammatory cytokines represent one critical link between maternal infection and any potential impact on offspring brain and behavior development. However, to what extent specific cytokines are necessary and sufficient for these effects remains unclear. It is also unclear how specific cytokines may impact the development of specific cell types Using a human cellular model, we recently demonstrated that acute exposure to interferon-ɣ (IFNɣ) recapitulates molecular and cellular phenotypes associated with neurodevelopmental disorders. Here, we extend this work to test whether IFNɣ can impact the development of immature glutamatergic neurons using an induced neuronal cellular system. We find that acute exposure to IFNɣ activates a signal transducer and activator of transcription 1 (STAT1)-pathway in immature neurons, and results in significantly increased major histocompatibility complex I (MHCI) expression at the mRNA and protein level. Furthermore, acute IFNɣ exposure decreased synapsin I/II protein in neurons but did not affect the expression of synaptic genes. Interestingly, complement component 4A (C4A) gene expression was significantly increased following acute IFNɣ exposure. This study builds on our previous work by showing that IFNɣ-mediated disruption of relevant synaptic proteins can occur at early stages of neuronal development, potentially contributing to neurodevelopmental disorder phenotypes.